PERAN TEKNOLOGI E-RETRIBUSI QRIS SEBAGAI MODERASI ATAS PENGARUH KOMPENSASI DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI DISPERINDAG KOTA PASURUAN - Wahyu Fitri Nucifera,; Muryati, Muryati; Nasharuddin Mas, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to obtain empirical evidence about the role of compensation and work ability in encouraging the improvement of Employee Performance of Department Industry and Trade of Pasuruan City. In addition, to obtain empirical evidence of the moderating ability of QRIS e-retribution technology.This type of research is quantitative with the SEM method. The data was obtained through a questionnaire which was distributed to 62 employees of Department Industry and Trade of Pasuruan City.Empirical evidence obtained is that work ability can play a strong role in encouraging employee performance improvement, but compensation cannot. However, if through the moderation of the QRIS e-retribution technology, both work ability and compensation, both play a strong role in improving the Employee Performance of Department Industry and Trade of Pasuruan City. This finding is supported by education that can develop talent, the longer the employee works the more able to understand his duties, the salary is in accordance with the regulations, obtains a pension fund, is able to learn quickly, QRIS increases productivity and enhances work effectiveness